2014
DOI: 10.1038/cddis.2014.66
|View full text |Cite
|
Sign up to set email alerts
|

Longikaurin A, a natural ent-kaurane, induces G2/M phase arrest via downregulation of Skp2 and apoptosis induction through ROS/JNK/c-Jun pathway in hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is the most common form of primary liver cancer, and is also highly resistant to conventional chemotherapy treatments. In this study, we report that Longikaurin A (LK-A), an ent-kaurane diterpenoid isolated from the plant Isodon ternifolius, induced cell cycle arrest and apoptosis in human HCC cell lines. LK-A also suppressed tumor growth in SMMC-7721 xenograft models, without inducing any notable major organ-related toxicity. LK-A treatment led to reduced expression of the proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 52 publications
2
57
1
2
Order By: Relevance
“…Overproduced ROS and free radicals lead to serious damage to lipids, proteins, and DNA, and regulate the process involved in the initiation of apoptotic signaling [29, 36]. ROS overproduction could induce the depolarization of the mitochondrial membrane, which eventually results in an increase in the level of other pro-apoptotic molecules in the cytosol [37].…”
Section: Discussionmentioning
confidence: 99%
“…Overproduced ROS and free radicals lead to serious damage to lipids, proteins, and DNA, and regulate the process involved in the initiation of apoptotic signaling [29, 36]. ROS overproduction could induce the depolarization of the mitochondrial membrane, which eventually results in an increase in the level of other pro-apoptotic molecules in the cytosol [37].…”
Section: Discussionmentioning
confidence: 99%
“…At the initial stage in HCC development, ROS or oxidative stress-responses mainly stimulate hepatocarcinogenesis or promote HCC development by activating pro-oncogenic gene activities or oncogenic signaling pathways such as mitogen-activated protein kinases (MAPKs) [3, 4]. Along with the progression of HCC, ROS overproduction or long-lasting oxidative stress-responses would tend to induce cell death or prevent cancer development in HCC [1, 5]. Therefore, modulating homeostasis of ROS or oxidative stress-responses has become an important therapeutic strategy for HCC [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the progression of HCC, ROS overproduction or long-lasting oxidative stress-responses would tend to induce cell death or prevent cancer development in HCC [1, 5]. Therefore, modulating homeostasis of ROS or oxidative stress-responses has become an important therapeutic strategy for HCC [5, 6]. Accumulative evidences support that oxidants have therapeutic effects in cancer treatment and the underlying mechanisms have been well studied [5, 7-11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ent-kaurane diterpenoids exhibit cytotoxic effects with the induction of ROS [23,24,33] . Consistently with the observations that oridonin and longikaurin A induce ROS-dependent inhibitory effects on cell proliferation, our study demonstrated that both JA and JB induced ROS production, which in turn led to the DNA damage response.…”
Section: Discussionmentioning
confidence: 99%